Bulgarian Cowpea Landraces—Agrobiological and Morphological Characteristics and Seed Biochemical Composition - Tsvetelina Stoilova; Lyudmila Simova-Stoilova (Agriculture)
To face climate change, searching for alternative crops resistant to drought and heat stress becomes necessary, along with efficient germplasm management. Old landraces well-adapted to local climatic conditions, pests, and pathogens could be used as a source of desired traits. Cowpea (Vigna unguiculata L. Walp.), grown mainly in the tropical and subtropical areas, presents superior drought and heat stress adaptation compared to other legumes. Limited information is available on field performance and nutrient qualities of cowpea landraces originating from southern Bulgaria. The aim of the present study was to compare in field conditions and their impacts on plant performance, yield, and the seed biochemical composition of Bulgarian cowpea accessions, including fourteen landraces and one variety. Higher-yielding, earlier-maturing accessions were discerned. Among the landraces studied, B1E0103 was the most productive under the agro-climatic conditions in Sadovo, central Bulgaria; BOE0035 had the earliest maturity. The seed moisture content was 11.5 ± 0.3%, and the energy value was 347.9 ± 1.2 kcal/100 g. The crude protein content varied from 22.5 to 27%, the lipids were 1.6–2.55%, the carbohydrates were 56.5–61.4%, ash was 3.8–4.3%, dietary fibers were 3.1–4.5%, tannins were 16–22%, phenols were 1.3–4.4 mg/g, flavonoids were 1.85–3.7 mg/g, and the trypsin-inhibiting activity was 0.7–2.5 units/mg FW, with the lowest in BOE0010, the variety “Hrisi”, and B1E0103 and the highest in B0E0035, A9E1230, and A8E0562. Landraces are promising genetic material for future research and breeding purposes.